Some Risk Factors of Atopic Dermatitis in Adults - Wong Hendra Wijaya; Arini Astasari Widodo; Fitria Jaya (Jurnal MedScientiae, 2023)
Atopic dermatitis (AD) is an inflammatory skin disorder characterized by intense itching and eczematous lesions. The onset of AD usually occurs in childhood and AD symptoms can last into adulthood. An increasing prevalence of AD has been observed worldwide. The causes of AD are multifactorial and there are still not many systematic reviews of AD-related risk factors. This study uses a literature review method. Literature search was conducted using Google Scholar and PubMed. using keywords: atopic dermatitis, risk factors, adults, and observational studies. All literature was selected using inclusion and exclusion criteria to assess the suitability of the content and quality of the study. Patients with atopic dermatosis had a filaggrin mutation cause loss/change in the function of filaggrin (Filament Aggregating Protein). Risk factors for atopic dermatitis in adults include a history of atopy, food allergies, a history of atopy in the father or mother or both, history of AD in parents, having pets at home, younger age or early onset, being a former smoker, gender women and active smoking, as well as passive smokers, low education level (<=12 years), socioeconomic status, and living in small places. Symptoms and clinical manifestations include pruritus, morphology and wide distribution of lesions, chronic and recurrent dermatitis, history of atopy and family history of atopy. Management of atopic dermatitis begins with education and skin care by taking regular baths and using emollients/moisturizers. Atopy and family history of atopy, smoking, low education, and socioeconomic are risk factors for AD in adults.